The Academic Archivist’s Fear of Popular Music - Silversides, Brock (CAML Review / Revue de l'ACBM, 2015)
This talk, delivered at the CAML Conference in Ottawa on June 4, 2015, examines a number of reasons for the reluctance of academic archivists/Special Collection librarians to acquire popular music fonds/collections. Arguments are put forward that popular music is an excellent indicator of the concerns of society and changes in culture, that it is worthy of scholarly research, and that as research trends are changing to incorporate popular music, so too should the collecting focus of music archivists/librarians.